Mephentermine dependence with induced psychosis: a series of two cases. (1st November 2020) - Vishwakarma, Anuranjan; Tarwani, Jatin; Chawla, Nishtha; Dayal, Prabhoo; Agrawal, Alok; Mandal, Piyali; Ambekar, Atul
ABSTRACT: Mephentermine is an α-adrenergic agonist, indicated for treatment of hypotensive states. It is not a common drug used for recreational purposes; rather for its performance enhancing properties. However, there are few case reports which highlight its dependence potential or its effect on induction of psychotic symptoms. In this case series, we intend to present cases of two individuals who used mephentermine as performance enhancer. Both showed significant improvement in short span of time on remaining abstinent from it. This highlights the common context of usage of mephentermine as performance enhancer leading to dependence and its effect on induction of psychosis in individuals with low genetic vulnerability.